ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PEGAWAI DI KANTOR KECAMATAN TAMBUN UTARA KABUPATEN BEKASI - Ega Permana Pradipa; Neny Marlina (Journal of Politic and Government Studies, 2026)
This study aims to analyze the level of public satisfaction with the services provided by employees at the Tambun Utara District Office, Bekasi Regency, and to identify the factors influencing the quality of public services. The research background is based on diverse public reviews, ranging from appreciation for fast and efficient services to complaints regarding delays, unclear procedures, and inadequate facilities. The research employs a qualitative approach with data collection techniques including in-depth interviews, observations, and documentation. The analysis is conducted using the five dimensions of service quality (Servqual) according to Kotler (2017), namely reliability, responsiveness, empathy, tangibles, and assurance. The findings indicate that although some residents are satisfied with administrative services such as ID cards and family cards that are processed quickly and free of charge, significant challenges remain, including delays in processing, lack of transparency, and suboptimal waiting room facilities. These results emphasize the need for continuous evaluation and improvement of public service quality at the district level to ensure equitable satisfaction among the community.